Fiber Bragg Grating Sensors: Recent Advancements, Industrial Applications and Market Exploitation - Cusano, Andrea; Cutolo, Antonello; Albert, Jacques (Bentham Science Publishers, 2011)
The book is an exciting source of information for individuals interested in learning about and marketing sensors. The book focuses on scientific and commercial advances in Fiber Bragg Grating (FBG) sensor technology since its discovery over 30 years ago. Discussions on new FBG sensor manufacturing and processing methods are provided by leading experts in the field. Novel applications of FBG sensor technology in engineering, energy, chemical and biological sectors are also included along with a clear identification of commercial opportunities in the next decade.